2010
DOI: 10.1111/j.1365-2133.2010.09809.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of nonmelanoma skin cancers in Alberta, Canada, 1988-2007

Abstract: NMSC incidence in Alberta has stabilized in women and declined in men. As 95-99% of NMSC occurs in patients aged 40 years or older, and with its increased frequency in traditionally clothed areas, the authors recommend regular complete skin examinations starting at 40 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 47 publications
9
69
0
5
Order By: Relevance
“…Similar findings have been reported. A study of patients from Alberta, Canada showed that the incidence rate for invasive SCC lesions was greater than that for in situ SCC lesions [7]. Furthermore, the gap between incident invasive and in situ SCC narrowed from 1990–1994 to 2000–2004 [7], similar to the rise in our ratios toward 1 in the NHS cohort.…”
Section: Discussionsupporting
confidence: 56%
“…Similar findings have been reported. A study of patients from Alberta, Canada showed that the incidence rate for invasive SCC lesions was greater than that for in situ SCC lesions [7]. Furthermore, the gap between incident invasive and in situ SCC narrowed from 1990–1994 to 2000–2004 [7], similar to the rise in our ratios toward 1 in the NHS cohort.…”
Section: Discussionsupporting
confidence: 56%
“…23 The lifetime risk has been estimated at more than 30% in a white German population, 24 28-33% in the US, 25 and 15-28% for women and 17-39% for men in Canada. 6 In Australia the lifetime incidence of BCC is now greater than 50% (C Del Mar, personal communication, 2012). About 75 000 new cases of BCC occur each year in the United Kingdom, and the incidence is predicted to rise up to the year 2040.…”
Section: Who Gets Bcc?mentioning
confidence: 99%
“…Of the non-melanoma skin cancers, 75-80% are BCCs 3-5 and up to 85% of these are on the head and neck. [4][5][6][7][8][9][10][11][12][13][14][15][16] The remainder are predominately squamous cell carcinomas. Delay in presentation is associated with increased tumour growth.…”
mentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is the most common form of skin cancer accounting for 90% of skin neoplasia [1]. It occurs in sun damaged skin particularly in the head and neck region, often on the face, and is generally a slowly progressive local disease.…”
Section: Introductionmentioning
confidence: 99%